Empowerment of Micro Entrepreneurs Providing Halal Canteens Through Training and Assistance - Oemar, Hirawati; Orgianus, Yan; Khuza’i, Rodliyah; Darusman, Fitrianti; Alifani, Ulima (KnE Social Sciences, 2023)
There has been government regulation regarding the obligation of product halal certification for all business groups, including microenterprises that sell canteen food. The existence of a halal certificate other than as an obligation is expected to increase consumer confidence in the certainty of product halalness and support the selling power of entrepreneurs. Some canteen food entrepreneurs have received socialization regarding the application of mandatory halal certification for their products, but there is no strong intention to obtain halal certification for their products. This study aims to empower micro-enterprises in increasing independence and awareness of halal products and overseeing the implementation of the halal product guarantee system. It is necessary to carry out empowerment activities through training and assistance to entrepreneurs to obtain halal certificates, such as advanced training in halal food knowledge; assistance in building a halal product guarantee system; filling out registration documents for halal certification requirements. The results of training and assistance for halal certification show an increased understanding of halal certification procedures and an increased readiness to implement a halal product assurance system, and 96.2% of canteen food micro-entrepreneurs stated that they would register their products to get halal certificates. Keywords: halal certification, micro-enterprises empowerment, training, assistance